How Do Ideas Travel? The Role of Epistemic Communities in the Social Policy Making Process in Latin America - Osorio Gonnet, Cecilia (Revista del CLAD Reforma y Democracia, 2017)
This article seeks to contribute to the understanding of the diffusion process of Conditional Cash Transfer Programs (CCTs) in Latin America and the role of experts -reunited in an epistemic community- and International Organizations (IOs). CCTs have been increasingly implemented worldwide in the last decades and, until 2010, 17 countries have adopted them in Latin America alone. The evidence suggests that this convergence is due to a policy diffusion process. After their implementation by regional pioneers -Brazil and Mexico- during the middle of the ‘90s, the programs caught the attention of International Organizations like the World Bank and the Inter-American Development Bank, which in turn contributed to their dissemination. These organizations supplied loans and technical advice, and also, they developed diverse activities, networks, papers and reports which have contributed to create a consensus on the efficiency of CCTs. Moreover, and taking an essential role, the existence of an epistemic community increased the available information on these programs and contributed to their legitimacy, playing a role in the domestic policy making process as well as in the adoption of CCTs by more countries. This matter deserves further attention in order to better understand the influence of ideas which can produce convergence of policies, the role of the actors involved and the relationship between the domestic and international level during the policy making process
Keywords: Social Policy; Policies Planning; Knowledge Management; Latin America